Understanding chemical reactions of CO2 and its isoelectronic molecules with 1-butyl-3-methylimidazolium acetate by changing the nature of the cation: The case of CS2 in 1-butyl-1-methylpyrrolidinium acetate studied by NMR spectroscopy and density functional theory calculations - Isabel Cabaco, M. (2017)
NMR spectroscopy (H-1, C-13, N-15) shows that carbon disulfide reacts spontaneously with 1-butyl-1-methylpyrrolidinium acetate ([BmPyrro][Ac]) in the liquid phase. It is found that the acetate anions play an important role in conditioning chemical reactions with CS2 leading, via coupled complex reactions, to the degradation of this molecule to form thioacetate anion (CH3COS-), CO2, OCS, and trithiocarbonate (CS32-). In marked contrast, the cation does not lead to the formation of any adducts allowing to conclude that, at most, its role consists in assisting indirectly these reactions. The choice of the [BmPyrro](+) cation in the present study allows disentangling the role of the anion and the cation in the reactions. As a consequence, the ensemble of results already reported on CS2-[Bmim][Ac] (1), OCS-[Bmim][Ac] (2), and CO2-[Bmim][Ac] (3) systems can be consistently rationalized. It is argued that in system (1) both anion and cation play a role. The CS2 reacts with the acetate anion leading to the formation of CH3COS-, CO2, and OCS. After these reactions have proceeded the nascent CO2 and OCS interact with the cation to form imidazolium-carboxylate ([Bmim] CO2) and imidazolium-thiocarboxylate ([Bmim] COS). The same scenario also applies to system (2). In contrast, in the CO2-[Bmim] [Ac] system a concerted cooperative process between the cation, the anion, and the CO2 molecule takes place. A carbene issued from the cation reacts to form the [Bmim] CO2, whereas the proton released by the ring interacts with the anion to produce acetic acid. In all these systems, the formation of adduct resulting from the reaction between the solute molecule and the carbene species originating from the cation is expected. However, this species was only observed in systems (2) and (3). The absence of such an adduct in system (1) has been theoretically investigated using DFT calculations. The values of the energetic barrier of the reactions show that the formation of [Bmim] CS2 is unfavoured and that the anion offers a competitive reactive channel via an oxygen-sulphur exchange mechanism with the solute in systems (1) and (2). (C) 2014 AIP Publishing LLC.